2003
DOI: 10.1182/blood-2002-01-0239
|View full text |Cite
|
Sign up to set email alerts
|

A role for apoptosis in the control of neutrophil homeostasis in the circulation: insights from CD18-deficient mice

Abstract: The control of neutrophil turnover in the circulation is a key event in homeostasis and inflammation. Using CD18-deficient (CD18 Ϫ/Ϫ ) mice that show a 19-fold increase of blood neutrophil counts when compared with wild-type animals (CD18 ϩ/ϩ ), we found that apoptosis of peripheral neutrophils was significantly reduced from 27.4% in the wild-type to 4.8% in CD18 Ϫ/Ϫ mice within 4 hours after isolation as measured by analysis of DNA content. This was confirmed by detecting CD16 expression, nuclear morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 26 publications
2
46
0
1
Order By: Relevance
“…The neutrophilia seen in these mice is not due to the passive accumulation of neutrophils in the vasculature, nor due to alterations in the marginating pool found in the lung, but is primarily caused by increased granulopoiesis (37,41). A reduction in neutrophil apoptosis may also contribute to neutrophilia in Itgb2 Ϫ/Ϫ mice (42). Previous studies have shown that IL-17A can act directly on BM stromal cells to produce G-CSF, up-regulate the cell surface expression of stem cell factor, as well as stimulate myeloid progenitor cell proliferation (36).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophilia seen in these mice is not due to the passive accumulation of neutrophils in the vasculature, nor due to alterations in the marginating pool found in the lung, but is primarily caused by increased granulopoiesis (37,41). A reduction in neutrophil apoptosis may also contribute to neutrophilia in Itgb2 Ϫ/Ϫ mice (42). Previous studies have shown that IL-17A can act directly on BM stromal cells to produce G-CSF, up-regulate the cell surface expression of stem cell factor, as well as stimulate myeloid progenitor cell proliferation (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased neutrophil numbers observed in both α4Δ/Δ and β2-/-mice at 96 hours post TG injection may suggest either delay in apoptosis, impaired clearance, or sustained neutrophil recruitment. Involvement of both α4 and β2 integrins in regulating apoptosis and/or clearing of apoptotic cells have been demonstrated; deficiency in β2 integrins leads to a delay in neutrophil apoptosis and their subsequent accumulation in the peritoneum [40,41], while α4 integrin on apoptotic cells assist in their phagocytosis [42]. Thus, absence of α4 integrins may affect clearance of α4Δ/Δ neutrophils, thereby resulting in increased neutrophil presence in the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…A series of molecular events is involved in PMN apoptosis and is dependent on numerous environmental factors (9). Recent reports have demonstrated that intracellular mechanisms, which determine the lifetime of PMN critically involve the differential expression of the Bcl-2 family members Bax-a and Bcl-Xi, that control the apoptotic machinery of PMN in vivo (15,69). The environmental factors in our coculture model that might be involved in regulating pro-and antiapoptotic genes of PMN in close contact with airway epithelial cells await further attention.…”
Section: Discussionmentioning
confidence: 99%